Concordance of PD-L1 Expression Between Core Biopsy and Resection Specimens of Non–Small Cell Lung Cancer. (August 2018) - Gradecki, Sarah E.; Grange, Jacob S.; Stelow, Edward B.
Abstract : The heterogeneity of programmed death ligand 1 (PD-L1) expression in non–small cell lung carcinomas (NSCLCs) is well studied; however, the method of tissue sampling needed to obtain adequate diagnostic material has not been established. This study aimed to determine whether core needle biopsy provides sufficient tissue for accurate PD-L1 evaluation despite tumor heterogeneity. A retrospective analysis comparing tumoral expression of PD-L1 in 51 lung core biopsies to subsequent resection specimens was performed. Scoring of membranous staining was categorized as 0%, 1% to 49%, and ≥50% of tumor cells. Staining ≥50% tumoral PD-L1 expression was detected in 8/51 (15.7%) of core biopsies and 8/51 (15.7%) of resection specimens. Core biopsy and resection results were concordant in 92.2% of cases (κ, 0.70; 95% confidence interval, 0.43-0.98). Therefore, despite tumor heterogeneity, detection of tumoral PD-L1 expression in NSCLC appears to be largely concordant between core biopsies and resection specimens, with the caveat that it may be helpful to reassess resection specimens for low-level staining. These findings suggest that core biopsy may be adequate for determining PD-L1 expression in NSCLC.